Screening with doppler ultrasound for carotid artery stenosis in patients with stroke or transient ischaemic attack. (7th August 2017) - Kristensen, Tatiana; Hovind, Peter; Iversen, Helle K.; Andersen, Ulrik B.
Summary: Introduction: Carotid endarterectomy of symptomatic internal carotid artery stenosis in patients with stroke or transient ischaemic attack reduces the risk of recurrent stroke, particularly if performed within 2 weeks from the first event. We evaluated the efficiency of a screening programme based on Doppler ultrasound in patients hospitalized with stroke or transient ischaemic attack in the stroke centre at Rigshospitalet, Glostrup, Denmark, concerning timeliness of referral to the vascular surgeon and performance of carotid endarterectomy according to national recommendations. Methods: Prospective study of a consecutive cohort of patients with transient ischaemic attack or stroke, referred for carotid Doppler ultrasound over a one‐year period. Results: We examined 1390 patients (1048 with stroke, 342 with transient ischaemic attack), 71% within 24 h and 93% within 4 days after admission. Carotid stenosis or occlusion was found in 171 patients (12·3%) and was hemisphere related in 78 patients (5·6%). Among these, 68 (87%) were referred to the vascular department, 94% within 4 days of admission. Carotid endarterectomy was performed in 16 patients, all within 14 days from admission, and was not declined in any patient due to procedural delay. Conclusions: In a major Danish stroke centre, the national recommended time limit of 4 days in patients with stroke or transient ischaemic attack for screening for carotid stenosis was met in almost all patients. No patients were excluded from surgery as a result of a time limit of 14 days from admission to surgery being exceeded. Of all patients screened, 1·2% underwent carotid endarterectomy.